A dictionary of varieties of English - Hickey, Raymond, 1954- (Malden, MA : Wiley-Blackwell, 2014)
'A Dictionary of Varieties of English presents a comprehensive listing of the distinctive dialects and forms of English spoken throughout the contemporary world. Provides an invaluable introduction and guide to current research trends in the field Includes definitions both for the varieties of English and regions they feature, and for terms and concepts derived from a linguistic analysis of these varieties Explores important research issues including the transportation of dialects of English, the rise of'New Englishes', sociolinguistic investigations of various English-speaking locales, and the study of language contact and change. Reflects our increased awareness of global forms of English, and the advances made in the study of varieties of the language in recent decades Creates an invaluable, informative resource for students and scholars alike, spanning the rich and diverse linguistic varieties of the most widely accepted language of international communication'--
Includes bibliographical references.
Print version record and CIP data provided by publisher.
Keywords: English language -- Variation -- Dictionaries; English language -- Dialects -- Dictionaries; English language -- Spoken English -- Dictionaries; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- General; English language -- Dialects; English language -- Spoken English; English language -- Variation; Electronic books; Dictionaries; Electronic books